The Managerial Roles of Sports Clubs CEOs in the Current and Desirable Conditions - Mahboobeh Surani; Rahim Ramezaninezhad; Noshin Benar; Hamidreza Goharrostami (The Society of Aging and Physical Activity (SAPA), 2014)
Today, the proper playing of managerial roles is of special importance in effective and successful management of sports clubs. The present paper aimed to study the managerial roles of sports clubs CEOs in Isfahan Province in the current and desirable conditions. Statistical population included all managers and directors of Sepahan, Zobahan, Foolad Mahan, and Gitipasand sports clubs (N=83), which was considered as the sample as well. An author-made questionnaire with 31 items on a Likert's 5-point scale was used for data collection. Validity of the questionnaire was confirmed by 15 experts and professors and its reliability was obtained α=0.94 by Cronbach's alpha coefficient. 84 questionnaires were handed out among all managers and directors of the studied sports clubs, 76 of which (91.5%) was returned. The results showed that priority of CEOs roles, respectively, include decisional role (4.16±0.61), informational role (4.09±0.56), and interpersonal role (4.03±0.67). The results of factor analysis also indicated that the roles of entrepreneurship, data collection, spokesman, and allocation of resources, respectively, are the most important roles of CEOs and negotiation, figurehead, and leadership roles are the least important ones in the desirable conditions. A significant difference was observed between the roles of managers in the current and desirable conditions (Sig.=0.001). The results suggested that the respondents' expectations of sports clubs CEOs' roles in desirable conditions is beyond their perceptions in the current situation. It can be generally concluded that sports clubs CEOs need to better perform all managerial roles, especially decisional role.